2022
DOI: 10.1037/edu0000764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of computer-based feedback on lower- and higher-order learning outcomes: A network meta-analysis.

Abstract: Feedback is one of the most important factors for successful learning. Contemporary computer-based learning and testing environments allow the implementation of automated feedback in a simple and efficient manner. Previous meta-analyses suggest that different types of feedback are not equally effective. This heterogeneity might depend on learner and test characteristics as well as the assessed outcome measure. Here, we present a novel network meta-analysis approach that allowed us to compare (i.e., rank) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 153 publications
2
6
0
Order By: Relevance
“…We recently reported that more elaborate forms of feedback (i.e. response‐oriented and conceptually‐focused feedback) provided a greater benefit to second‐year medical students than binary right/wrong feedback, 32 a finding congruent with the broader literature 37 . Building upon these findings, the current study aims to determine whether the timing of feedback has an effect on its efficacy as a tool for learning in medical education.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…We recently reported that more elaborate forms of feedback (i.e. response‐oriented and conceptually‐focused feedback) provided a greater benefit to second‐year medical students than binary right/wrong feedback, 32 a finding congruent with the broader literature 37 . Building upon these findings, the current study aims to determine whether the timing of feedback has an effect on its efficacy as a tool for learning in medical education.…”
Section: Introductionsupporting
confidence: 55%
“…response-oriented and conceptually-focused feedback) provided a greater benefit to second-year medical students than binary right/wrong feedback, 32 a finding congruent with the broader literature. 37 Building upon these findings, the current study aims to determine whether the timing of feedback has an effect on its efficacy as a tool for learning in medical education. In general, spacing learning opportunities over time to form distributed practice (as opposed to 'massed practice') appears to benefit clinical learning.…”
mentioning
confidence: 99%
“…Thus, in future research, additional moderators need to be investigated. In other learning contexts, the type of feedback has been shown to moderate effectiveness (Van der Kleij et al, 2015 ; Wisniewski et al, 2020 ; Mertens et al, 2022 ). In the context of AWE feedback, we need more primary studies that compare different types of feedback or at least provide sufficient information on the details of their feedback intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in education, we will find that collecting process data in the context of formative assessments for learning, such as incorporated in computer-based systems (intelligent tutoring systems; see, e.g., Aleven et al, 2010), will become increasingly common in everyday educational settings. Formative assessment results and fine-grained process data can provide valuable additional information for teachers and learners in terms of learning analytics and can, for example, establish the base for the provision of targeted, individualized automated feedback (e.g., Kuklick & Lindner, 2021, 2023; Kuklick et al, 2023; Mertens et al, 2022) and other types of status reports of students’ individual learning progression (e.g., directed at students, parents, teachers, or stakeholders). Thus, in the future, we may expect to see a closer relationship and an overlap between process data research in the assessment context and research in classroom learning settings.…”
Section: Discussionmentioning
confidence: 99%